Unidade autônoma de manejo da irrigação de baixo custo controlado via aplicativo para cultivos em ambiente protegido - Rolim, Talyson Weber Rodrigues (2021)
Given the constant increases in water costs, in addition to the limited amount of this resource, the automation of irrigation systems can help producers reduce expenses and increase production, consequently, profitability. Therefore, the objective of this research was to develop and test a prototype of an autonomous irrigation system with low cost for the management of irrigation in the production of vegetables, generating labor savings, analyzing its performance and its economic implications. The experiment was carried out in a greenhouse of the Department of Agricultural Engineering - DENA, located at the meteorological station of the Federal University of Ceará - UFC, PICI campus, in Fortaleza - CE. The culture used was rocket (Eruca Sativa L), cultivated in two production cycles in the period between December 17, 2020 and January 16, 2021 and between February 1 and March 3, 2021. The experiment was carried out in randomized blocks with 4 types of irrigation management, divided into automatic and manual: automatic soil management (IAS); automatic handling via climate (IAC), manual handling via soil (IMS) and manual handling via climate (IMC). Each treatment had 8 repetitions, totaling 32 experimental plots. Growth data such as plant height, number of leaves and production data such as fresh and dry mass of shoots were collected. Statistical analysis was used by the F test (ANOVA) for the studied factors and when they were evaluated, the Tukey test was performed, both at 5% probability. For the variable fresh mass, it was observed that the treatments IAC (17.75 g plant-1), IAS (12.38 g plant-1) and BMI (8.63 g plant-1) in cycle 1 were statistically related between each other by the Tukey test at 5% probability, in cycle 2 only the treatments IAC (16.29 g plant-1) and IAS (19.80 g plant-1) had this statistical similarity. The IAC and IAS treatments obtained the best results both in cycle 1 and in the second. Both managements (IAS and IAC) are recommended based on this research, however, considering the financial difficulties of the small producer, BMI can be considered a desirable option in unfavorable economic conditions.